(untitled) (INNOVATIVE ECONOMY, 2025)
Sadovska I.B., Nahirska K.Ye., Putsenteilo P.R. ORGANIZATIONAL AND ECONOMIC MECHANISMS OF GRANT PROJECT MANAGEMENT IN THE ENERGY INDUSTRY Purpose. The aim of this article is to establish the theoretical foundations and identify approaches to developing organizational and economic mechanisms for managing grant projects in the energy sector. Methodology of research. The methodological foundation of this study is based on systemic and institutional approaches, which allow for the examination of grant project management as a complex economic phenomenon. Methods of analysis and synthesis were applied to synthesize scientific approaches; comparative analysis was used to examine domestic and international experience. Using a structural-functional approach, the components of the management mechanism were substantiated and the processes of grant project implementation were modeled. Findings. The principles for managing grant projects in the energy sector have been defined. A conceptual model of the organizational and economic mechanism has been developed, covering institutional, financial, organizational, and informational components. A system of indicators for evaluating the effectiveness of grant project implementation has been established, taking into account economic, environmental, and social factors. Originality. The approach to the formation of an organizational and economic mechanism for managing grant projects by integrating a risk-oriented approach, ESG approaches and digital analytical tools has been improved. Theoretical provisions regarding the role of grant funding as a factor in improving energy security and innovative transformation of the industry have gained further development. Practical value. The proposed provisions should be used by energy industry enterprises, state administration bodies and development institutions when implementing and supporting grant projects. Their practical application will contribute to increasing the efficiency of the use of resources, strengthen the transparency of management, minimize risks, and improve the toolkit for achieving the strategic goals of the sustainable development of the state’s energy industry. Key words: grant projects, grant activities, energy industry, project management, organizational and economic mechanism, energy security, innovative development, ESG, efficiency, state regulation.